BEBERAPA TITIK KRITIS MURABAHAH DALAM FATWA DSN - Husni Husni (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
A reality that can not be denied is the dominance of murabaha as a financing contract in sharia financial institutions. The dominance is also included in the number of fatwas that regulate murabaha. The number of fatwas, indirectly implies the number of